2015
DOI: 10.1080/02602938.2015.1054783
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development in higher education: evaluating coherence between theory andpraxis

Abstract: Universities are an important part of the process of change taking place in society. However, this is often overshadowed by these institutions giving priority to technocratic models in the relationship between science and society. In this context, according to Habermas, theories can serve to clarify practical questions and guide praxis into the right actions (social emancipation and rational autonomy). Habermas introduces the need to evaluate the particular contexts in which scientific arguments are made and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…It is necessary to acknowledge that technologies can reduce the need for human and financial resources; however, it should be understood that putting a huge amount of effort into the development of technologies will see a weak outcome if no corresponding effort is put into human resource development to support people's digital competency. As Amador et al [50,57] concluded in their research that staff development and organizational changes are needed to support Sustainable education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to acknowledge that technologies can reduce the need for human and financial resources; however, it should be understood that putting a huge amount of effort into the development of technologies will see a weak outcome if no corresponding effort is put into human resource development to support people's digital competency. As Amador et al [50,57] concluded in their research that staff development and organizational changes are needed to support Sustainable education.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, it is argued, is the foundation for sustainable education, i.e., education where teachers are the drivers of this process-to remain open to change, questioning the epistemological backgrounds upon which they base institutional management and teaching [48]. Some researchers point out that sustainability of higher education is possible if organizational changes are made in the higher education process itself [48] and in curriculum redesign to develop sustainable education [9,49,50].…”
Section: Tel For Sustainable Educationmentioning
confidence: 99%
“…Thus, the acceptability of value-laden commitments to sustainability is a fraught issue in university contexts of academic neutrality, neoliberalisation and industry relationships (Mulder 2010). These pressures have contributed to the mainstreaming of conventional ecological modernisation arguments in ESD (e.g., Coffey and Marston 2013), Amador et al (Amador et al 2015) conclude that the slow institutionalization of ESD is due to the resistance of universities to addressing the ideological and political challenges that strong sustainable development commitments suggest. This and other obstacles suggest that we are still some distance from developing transformative ESD courses that challenge the mainstream (for example see Sipos et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…UNESCO at the Johannesburg World Summit on Sustainable Development in 2002 highlighted the importance of education as the heart of sustainable development [9]. Likewise, a report from the United Nations Conference on Sustainable Development highlighted the importance of education in preparing people to implement sustainable development [10].…”
Section: Introductionmentioning
confidence: 99%